VIABILITY OF FIBROBLASTS OF TUGAI DEER (CERVUS HANGLU BACTRIANUS LYDEKKER, 1900) DURING CRYOPRESERVATION BY DIFFERENT METHODS - Nurkenov, T.T.; Zima , Y.A.; Katubayeva , B.S.; Grachev , A.A.; Baidavletov , Y.R.; Toishybek , D.Y.; Salmenova, M.Y.; Assanova, Y.A.; Toishibekov , Y.M. (Eurasian Journal of Applied Biotechnology, 2025)
Currently, there is a rapid and continuous decline in wild animal populations, which threatens accelerated loss of biodiversity on a global scale. Along with in situ conservation strategies, ex situ conservation measures such as germplasm cryopreservation should be widely applied. Cryopreservation in combination with assisted reproductive technologies can become an important means of successfully preserving the biodiversity of the animal world. Methods based on obtaining cell cultures are of great importance in scientific research. The resulting cell lines can be frozen and stored in containers with liquid nitrogen for many years. Such cell and tissue biobanks represent a viable source of genetic material and living cells that offer numerous opportunities for further research. The aim of this study was to investigate the scientific basis for cryopreservation of somatic cells of tugai deer, which is a species in need of special protection. Studies were conducted on the viability of tugai deer fibroblasts using various cryopreservation methods. The viability of frozen-thawed tugai deer fibroblasts was determined, and it was shown that the most effective cryopreservation of this species fibroblasts was the use of a cryoprotectant 1.5 M ethylene glycol and a slow equilibrium freezing mode using a programmed freezer.